2007
DOI: 10.1890/06-1993.1
|View full text |Cite
|
Sign up to set email alerts
|

Native Plant Diversity Resists Invasion at Both Low and High Resource Levels

Abstract: Human modification of the environment is causing both loss of species and changes in resource availability. While studies have examined how species loss at the local level can influence invasion resistance, interactions between species loss and other components of environmental change remain poorly studied. In particular, the manner in which native diversity interacts with resource availability to influence invasion resistance is not well understood. We created experimental plant assemblages that varied in nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
143
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(165 citation statements)
references
References 47 publications
16
143
4
2
Order By: Relevance
“…We also examined how native species diversity influenced the performance of Centaurea stoebe L., which is a potent invader in North America but is native to Europe, where our experiment was conducted. In a similar diversityinvasibility experiment previously conducted in North America, Marler (2007, 2008) found that C. stoebe heavily invaded low-diversity assemblages but performed more poorly in high-diversity plots. Thus, our goal was to determine whether C. stoebe responded similarly to diversity in its native range.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…We also examined how native species diversity influenced the performance of Centaurea stoebe L., which is a potent invader in North America but is native to Europe, where our experiment was conducted. In a similar diversityinvasibility experiment previously conducted in North America, Marler (2007, 2008) found that C. stoebe heavily invaded low-diversity assemblages but performed more poorly in high-diversity plots. Thus, our goal was to determine whether C. stoebe responded similarly to diversity in its native range.…”
Section: Introductionsupporting
confidence: 54%
“…To facilitate comparison of the data from our experiment with those reported by Marler (2007, 2008), we used the same methods for selecting native plant species and constructing experimental plant assemblages as those described in Maron and Marler (2008). Plant assemblages varied in both species (two to 16 species) and functional groups richness (one to six functional groups; table 1).…”
Section: Experimental Design Of the Garden Plotsmentioning
confidence: 99%
See 3 more Smart Citations